Similarities in element content between comet 67P/Churyumov–Gerasimenko coma dust and selected meteorite samples - Oliver J. Stenzel; Martin Hilchenbach; Sihane Merouane; John Paquette; Kurt Varmuza; Cécile Engrand; Franz Brandstätter; Christian Koeberl; Ludovic Ferrière; Peter Filzmoser; Sandra Siljeström; COSIMA team (United Kingdom, 2022)
We have analysed the element composition and the context of particles collected within the coma of 67P/Churyumov–Gerasimenko with Rosetta’s COmetary Secondary Ion Mass Analyzer (COSIMA). A comparison has been made between on board cometary samples and four meteorite samples measured in the laboratory with the COSIMA reference model. Focusing on the rock-forming elements, we have found similarities with chondrite meteorites for some ion count ratios. The composition of 67P/Churyumov–Gerasimenko particles measured by COSIMA shows an enrichment in volatile elements compared to that of the investigated Renazzo (CR2) carbonaceous meteorite sample.